POLICY ENTREPRENEURS DAN JARINGAN KEBIJAKAN PENGENTASAN KEMISKINAN DI ERA DESENTRALISASI - Ronald Philips Letor (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2021)
One of the mainstream poverty indicators in poverty alleviation policies in Indonesia is the condition of the houses occupied by the community members. This indicator is determined by the Central Bureau of Statistics to assess the appropriateness of community houses based on building materials, health requirements and ownership. This provokes/ nudges the central and local governments to formulate policies for the improvement and construction of liveable houses for low-income people. Instead of functioning as poverty alleviation efforts, policy entrepreneurs have highlighted the issue of traditional architecture based on environmentally friendly, disaster friendly and energy efficient, so that this poverty program has failed to be integrated since the agenda setting stage. This study employed the qualitative method with a document analysis approach to elaborate the structural conditions and policy networks that caused the failure and its implications through a case study of the Unfit Home Improvement (Rutilahu) program during the era of Governor of West Java 2013-2018, Achmad Heriawan